THE ASSESSMENT OF COMPANY PERFORMANCE USING BALANCE SCORECARD ANALYSIS - Sukmo Hadi Nugroho; Elisabeth Tanti Pudiastuti (JOURNAL ASRO, 2020)
Currently, the performance analysis of a company is the most needed thing in achieving the vision and mission of the organization. The purpose of this study is to determine the company's performance in terms of financial and non-financial performance using the Balanced Score Card approach through four perspectives, namely: (1) finance, (2) customers, (3) internal business, and (4) growth and learning. . The data collection method was done by qualitative and quantitative. The results of this study note that the performance of PT. Contractor Company Tbk, Tbk has been very good. From a financial perspective, it can be seen that the company's ability to guarantee short-term and long-term debt is quite good and the company's ability to get a good profit, as seen from the value of the Net profit margin. From the customer perspective, the results of the customer satisfaction survey are quite good. The level of employee satisfaction is quite good. As for the internal business, the effectiveness of the use of operating expenses was successfully realized by the company. Keywords: Company Performance, Balance Score Card